Language Styles In Fiersa Besari’s Twitter - Maqdisa Azzahra (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the style of language on Twitter Social Media from the Fiersa Besari account. The purpose of this study is to identify the style of language used by Fiersa Besari in Twitter updates and to describe the types of language style that occurs in Fiersa Besari's Twitter updates. Twitter application users are generally adults and Fiersa Besari is the object of researcher to conduct research related to language style. The researcher uses Qualitative methods because research is based on data in the form of sentences and clauses. The data is taken from several updates from Twitter users to get the right data. To collect data, the researcher uses the theory from Martin Joos (1976). The researcher identifies and describes all the reforms related to language style based on Language Style: Frozen style, Formal, Consultative, Casual, and Intimate style. The types of language styles found in the data from the results of this analysis are Frozen, Formal, Consultative, Casual, and Intimate styles.